Predicting C282Y Homozygote Genotype for Hemochromatosis Using Serum Ferritin and Transferrin Saturation Values from 44,809 Participants of the HEIRS Study - Andrew Lim; Mark Speechley; Paul C Adams (Canadian Journal of Gastroenterology and Hepatology)
INTRODUCTION: The simultaneous interpretation of serum ferritin level and transferrin saturation has been used as a clinical guide to diagnose genetic hemochromatosis. The Hemochromatosis and Iron Overload Screening (HEIRS) Study screened 101,168 North American participants for serum ferritin level and transferrin saturation, and C282Y genotyping for the HFE gene.